Peran Bimbingan Badan Penasehatan, Pembinaan, Dan Pelestarian Perkawinan (BP4) Dalam Mencegah Perceraian Di KUA BPR Ranau Tengah - Rati Lastari; Suryati Suryati; Muzaiyanah Muzaiyanah (Social Science and Contemporary Issues Journal, 2024)
The title of this research is "The Role of BP4 Guidance (Marriage Advisory, Development and Preservation Agency) in Preventing Divorce in KUA BPR Ranau Tengah". As is known, a role is someone who is a part of or is a prominent leader in an event. Apart from that, role is an explanation that refers to the social science connotation which defines role as a function that a person carries out when occupying a characteristic (position) in the social structure. The problem in this research is: What is the role of BP4 Guidance (Marriage Advisory, Development and Preservation Agency) in preventing divorce at KUA BPR Ranau Tengah? The aim of this research is to determine the role of BP4 Guidance (Marriage Advisory, Development and Preservation Agency) in preventing divorce at KUA BPR Ranau Tengah.